Sanitizer Dosing Decoupling Control Based on IMC-NN Inverse System - Xie Peizhang; Zhou Xingpeng (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Multi tunnels multi pools (MTMP) structure is very common in tap-waterworks, MTMP structure sanitizer dosing system is a complicated system with coupling, large time delay and inertial. Internal model control decoupling based on wavelet neural networks inverse system is introduced to solve the problems. First  order inverse system is identified using wavelet neural networks, this inverse system cascades the original system so that pseudo-linearization system can be obtained, and then this MIMO system can be transformed to SISO system with no coupling. In addition time delay and model error can be overcome by internal model control. Practical application shows that the coupling, time delay and inertial of MTMP sanitizer dosing system is overcome, also this method is able to resist the disturbance and improve the robustness.DOI: http://dx.doi.org/10.11591/telkomnika.v11i9.3247